The Role of the AggR Regulon in the Virulence of the Shiga Toxin-Producing Enteroaggregative Escherichia coli Epidemic O104:H4 Strain in Mice - Boisen, Nadia; Melton-Celsa, Angela R.; Hansen, Anne-Marie; Zangari, Tonia; Smith, Mark A.; Russo, Lisa M.; Scheutz, Flemming; O’Brien, Alison D.; Nataro, James P. (Frontiers in Microbiology, 2019)
An O104:H4 Shiga toxin (Stx)-producing enteroaggregative Escherichia coli (EAEC) strain caused a large outbreak of bloody diarrhea and the hemolytic uremic syndrome in 2011. We previously developed an ampicillin (Amp)-treated C57BL/6 mouse model to measure morbidity (weight loss) and mortality of mice orally infected with the prototype Stx-EAEC strain C227-11. Here, we hypothesized that mice fed C227-11 cured of the pAA plasmid or deleted for individual genes on that plasmid would display reduced virulence compared to animals given the wild-type (wt) strain. C227-11 cured of the pAA plasmid or deleted for the known pAA-encoded virulence genes aggR, aggA, sepA or aar were fed to Amp-treated C57BL/6 mice at doses of 1010-1011CFU. Infected animals were then either monitored for morbidity and lethality for 28 days or euthanized to determine intestinal pathology and colonization levels at selected times. The pAA-cured, aggR, and aggA mutants of strain C227-11 all showed reduced colonization at various intestinal sites. However, the aggR mutant was the only mutant attenuated for virulence as it showed both reduced morbidity and mortality. The aar mutant showed increased expression of the aggregative adherence fimbriae (AAF) and caused greater systemic effects in infected mice when compared to the C227-11 wt strain. However, unexpectedly, both the aggA and aar mutants displayed increased weight loss compared to wt. The sepA mutant did not exhibit altered morbidity or mortality in the Amp-treated mouse model compared to wt. Our data suggest that the increased morbidity due to the aar mutant could possibly be via an effect on expression of an as yet unknown virulence-associated factor under AggR control.